On the field validation of α-μ fading coefficients estimator based on the autocorrelation function for ionospheric amplitude scintillation. Issue 10 (15th November 2019) - Marini-Pereira, Leonardo; Oliveira, Kelias de; Salles, Lucas A.; Moraes, Alison de O.; de Paula, Eurico R.; Muella, Marcio Tadeu de Assis Honorato; Perrella, Waldecir J.
Abstract: The ionosphere in low-latitude regions has intense dynamics with great variability – not only spatially but also temporally. The most critical effect found in the low-latitude region is the scintillation in phase and amplitude due to plasma bubble occurrence in the ionospheric layer. To augmentation systems like GBAS or SBAS, designed to provide Category-I (CAT I) precision approach service in low-visibility conditions, plasma bubbles can compromise the performance requirements for air navigation precision approach in a way that the service provided by the system is considered unviable. In practical terms, this is the main reason why the Brazilian Department of Airspace Control (DECEA) still has not implemented any augmentation system in Brazil. Scintillation may lead to loss of signal lock of the affected satellite. In this context, a better understanding of the scintillation pattern and its statistical properties gain particular relevance, once this is the most concerning issue for the performance of any GNSS receiver in low-latitude regions especially in the context of augmentation systems for air navigation. Previous works validated the use of the α-μ distribution to characterize amplitude scintillation. The present work is concerned with proposing a new method for the estimation of the α-μ coefficients based on the α-μ autocorrelation function. The method is validated using field data and comparing the results from empirical autocorrelation function with the results obtained from the moment-based estimator. Additionally, the efficiency of the method is proven by analyzing measurements of Level-Crossing Rate (LCR) and Average Fading Duration (AFD) with their respective theoretical formulation.